Synthesis and intramolecular nitrile oxide cycloaddition of 3,5 `-ether-linked pseudooligosaccharide derivatives: an approach to chiral macrooxacycles - Sengupta, J.; Mukhopadhyay, R.; Bhattacharjya, A.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Journal of Organic Chemistry, 2005)
[GRAPHIC] 3,5'-Ether-linked pseudooligopentose derivatives were synthesized for the first time from readily available carbohydrate precursors. The 1,2-isopropylidene-protected ether-linked oligopentoses are potentially important as precursors of novel RNA analogues. Intramolecular cycloaddition of the nitrile oxides prepared from these derivatives led to the diastereoselective formation of chiral isoxazolines fused to 10-16-membered oxacycles. The stereochemistry of some of these isoxazolines was established by X-ray diffraction and NOESY analysis.

Structure-property relationship of different types of polyester industrial yarns - Samui, Barun Kumar; Prakasan, Manikanda Priya; Ramesh, C.; Chakrabarty, Debabrata; Mukhopadhyay, R. (Journal of the Textile Institute, 2013)
Four major types of polyester industrial yarns (1000 Denier) which are used commercially were studied for their key structural parameters. An attempt has been made to establish a relationship between morphology and properties of these yarns. High tenacity (HT) polyester yarn has the highest birefringence, amorphous orientation, and long period but is relatively less crystalline. High shrinkage characteristic of HT polyester yarn can be accounted for its higher amorphous orientation. High modulus low shrinkage (HMLS) polyester yarn has higher crystallinity and crystal size compared to HT yarn. Fraction of tie molecules of these yarns has been calculated and found that low shrinkage (LS) and super low shrinkage (SLS) yarns have lesser tie molecules. These LS and SLS yarns are tailor-made to achieve lower shrinkage and at the same time maintaining a good level of tenacity. This is achieved with lower amorphous orientation in the final drawn yarn structure. Amorphous orientation was found to have stronger influence than any other structural parameter on the key yarn properties like modulus, tenacity, elongation, and shrinkage.
Keywords: modulus; orientation; polyester; shrinkage; structure

Studies on the static and dynamic properties of different types of polyester industrial yarns - Samui, Barun Kumar; Dasgupta, Saikat; Mukhopadhyay, R.; Ramesh, C.; Chakrabarty, Debabrata (Journal of the Textile Institute, 2016)
Four major types of polyester industrial yarns, viz. high tenacity (HT), high modulus low shrinkage (HMLS), low shrinkage (LS) and super low shrinkage (SLS) polyester yarns, were studied for their static and dynamic properties. An attempt has been made to establish a linkage between static and dynamic properties of these yarns with its structure and with its end applications. HMLS and HT polyester yarns have lower tan delta and work loss, which are the desired characteristics required for its end applications which include tire and conveyer belt. Higher overall orientation and higher fraction of tie molecules helped to achieve these properties in HT and HMLS polyester yarns. LS and SLS polyester yarns are mostly used for static applications. Low thermal shrinkage is the key requirement for the downstream processes of these yarns. Lower amorphous orientation in these two yarns is primarily responsible for achieving very low thermal shrinkage. A good co-relation has been established between the peak temperature of work loss (in slow speed hysteresis test) and the peak temperature of tan delta (in high-speed dynamic test).
Keywords: creep; modulus; polyester; shrinkage; tan delta; work loss